Introducing primary care research teaching in Ukraine: description and evaluation of the 'ABC' research methods course. Issue 1 (2nd January 2021) - Harris, Michael; Kolesnyk, Andriy; Taylor, Gordon; Kolesnyk, Pavlo
ABSTRACT: Ukraine has a developing and expanding system of general practice, but only a rudimentary academic primary care system and no research skills training for general practitioners (GPs). We designed and evaluated a transnational primary care research skills course for Ukrainian GPs. The ABC course is series of three 2-day workshops, designed to teach the basics of primary care research to early-career Ukrainian GPs. It was delivered by Ukrainian and British experts, using innovative, interactive teaching methods. Evaluation measures included participants' assessment of their research abilities, and changes in their attitudes, intentions and actions regarding their research practice. Seventeen Ukrainian GPs took part. There was a 1.32-point increase in research ability self-assessment 5-point Likert scores, with particular increases in literature review and budgeting abilities. Scores for research attitudes, intentions and actions increased by 4.0%, though limited by a ceiling effect. Many participants subsequently developed their own research projects, and some set up primary care research skills courses in their own Ukrainian academic organisations. The course resulted in increased levels of self-confidence and ability to plan primary care research, with improvements in participants' stages of change. It sets out a model for providing and evaluating innovative educational interventions in post-soviet countries, and gives them a basis for high-quality primary care research.